Leitura como atividade humana: Pra que que a gente lê? - Maira Tomayno de Melo Dias (2015)
This study aims to analyze contrastively the relationships between the reading activities experienced by children and young people and adults. We present the results of a longitudinal survey that focused on two initial literacy classrooms of two different public schools located in Belo Horizonte, Minas Gerais, Brazil. Data collection was carried out for three years year through participant observation, field notes, artifact analysis group, interviews, photographs, video and audio recordings. The theoretical-methodological approach adopted in the review process of our research is based on the historical-cultural approach to building knowledge of Lev S. Vygotsky (Vygotsky, 1927/2013, 1929/2000, 1930/2009, 1931/2012, 1933 / 2008); in development studies and learning (Bruner, 1997; GOMES, 2004; FREITAS 2007; GOMES, MONTEIRO, 2005; GOMES, DIAS & SILVA, 2008; GOMES, MORTIMER & Kelly, 2011; GOMES, FONSECA, DIAS & VARGAS 2011 ; VARGAS, GOMES, 2013) on literacy, literacy and language (STREET, 1984, 1995, 2002, 2003; BAKHTIN, 1992; FREIRE, 1980, 1988; ROJO, 2004, 2009; SOARES, 1998, 2003, 2004) and the contributions of Ethnography interactional (SBCDG, 1992; CASTANHEIRA, 2004). At the end of the research it was possible to know who read what, how, under what conditions and for what. Thus, it stood out the similarity and differences between the two classrooms. It became apparent that, in the classroom emotions and feelings are not separate cognition in the human development process. It was possible to conclude that affection is an important factor in interpersonal relationships built in the classroom as well as on disposal of the students on the reading activities proposed and developed since they constitute essentially human activity.